2021
DOI: 10.1186/s12889-021-10280-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of aircraft noise annoyance and noise sensitivity in the association between aircraft noise levels and medication use: results of a pooled-analysis from seven European countries

Abstract: Background Few studies have considered aircraft noise annoyance and noise sensitivity in analyses of the health effects of aircraft noise, especially in relation to medication use. This study aims to investigate the moderating and mediating role of these two factors in the relationship between aircraft noise levels and medication use among 5860 residents of ten European airports included in the HYENA and DEBATS studies. Methods Information on aircr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…Similarly, a higher risk for psychological distress was observed for people being extremely annoyed by noise in comparison to a lower risk for people being less annoyed [9]. Baudin et al [10] found an association between aircraft noise annoyance and the use of anxiolytics (medication for anxiety disorders), implying a mediating role of annoyance for the link of aircraft noise exposure to mental health outcomes.…”
Section: Noise Annoyance-a Mediator Of Aircraft Noise Effects On Health?mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a higher risk for psychological distress was observed for people being extremely annoyed by noise in comparison to a lower risk for people being less annoyed [9]. Baudin et al [10] found an association between aircraft noise annoyance and the use of anxiolytics (medication for anxiety disorders), implying a mediating role of annoyance for the link of aircraft noise exposure to mental health outcomes.…”
Section: Noise Annoyance-a Mediator Of Aircraft Noise Effects On Health?mentioning
confidence: 99%
“…No association was found for aircraft noise exposure and the use of medication indicated for mental health issues [10], and psychological distress measures [9]. However, in another study significant differences regarding depression scores between high exposure groups and the control group were observed [35].…”
Section: Mental Health and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Baudin, 2018 [15] Aircraft noise and psychological ill-health: the results of a crosssectional study in France France Baudin, 2021 [45] The role of aircraft noise annoyance and noise sensitivity in the association between aircraft noise levels and medication use: results of a pooled analysis from seven European countries UK, Germany, Netherlands, Sweden, Italy, Greece, France Beutel, 2016 [43] Noise annoyance is associated with depression and anxiety in the general population-the contribution of aircraft noise Germany Beutel, 2020 [40] Noise annoyance predicts symptoms of depression, anxiety, and sleep disturbance 5 years later. Findings from the Gutenberg Health Study Germany Eze, 2020 [29] Incidence of depression in relation to transportation noise exposure and noise annoyance in the SAPALDIA study Switzerland Floud, 2011 [44] Medication use in relation to noise from aircraft and road traffic in six European countries: results of the HYENA study UK, Germany, Netherland, Sweden, Italy, Greece…”
Section: Study Title Countrymentioning
confidence: 99%
“…Annoyance is not only regarded as a primary adverse effect of aircraft noise, but is assumed to be part of the causal pathway of other health outcomes and thus seems to mediate the effect of aircraft noise exposure and health risks [20]. Studies suggest that people reporting high levels of annoyance to have a higher risk for hypertension [21][22][23], a decrease in reported physical well-being [24], higher psychological distress [25], and, finally, an association was found between noise annoyance and the use of medication to treat anxiety disorders [26]. In addition, noise annoyance was observed to have an effect on sleep quality [5] and physical activity [27].…”
Section: Introductionmentioning
confidence: 99%